Psychological Trends in 21st Century Urdu Fiction - Qudratullah Khan; Dr.Sattar Khan Khattak; Dr.Syed Zubair Shah (Zaban-o-Adab, 2023)
The 21ST century saw a rise in popularity of Urdu short stories. Straightforward, storytelling made the text thrive. The terrorist attack on the Twin Towers and the beginning of the twenty-first century; this catastrophe had an impact on world politics and culture. The global terrorism problem had an impact on numerous countries. Many countries, like Pakistan, have grappled with instability, confusion, and uncertainty as prime targets of terrorism. To survive, the current "Urdu short story" must reflect contemporary themes. The circumstances also led to widespread psychological problems. This clarifies the powerful experience of psychological phenomena like panic, dread, and lack of identity, loneliness, alienation, and social suffocation in the "Urdu short story." Finally, skilled writers have been producing short stories in Urdu for centuries. Urdu fiction has used symbolism and psychological tenets in the twenty-first century. Contemporary Urdu short stories feature characters that are affected by a range of mental illnesses, such as schizophrenia, sadism, masochism, Transvestism, paraphilia, pedophilia, nostalgia, and others. This research is exploring the psychological impacts in the Urdu fiction in the 21st century to closely evaluate each of these qualities.